2017
DOI: 10.1159/000485616
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Network a Protective Factor for Cognitive Impairment in US Chinese Older Adults? Findings from the PINE Study

Abstract: Background: Social network has been identified as a protective factor for cognitive impairment. However, the relationship between social network and global and subdomains of cognitive function remains unclear. Objective: This study aims to provide an analytic framework to examine quantity, composition, and quality of social network and investigate the association between social network, global cognition, and cognitive domains among US Chinese older adults. Methods: Data were derived from the Population Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
(58 reference statements)
1
39
0
Order By: Relevance
“…Prior cross-sectional investigations have found that having a greater portion of family within one’s social network is associated with lower cognition (Li & Dong, 2018; Sharifian et al, 2019). Furthermore, having a higher number of close friends, but not children or neighbors, has been linked to better global cognition (Wang, He, & Dong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Prior cross-sectional investigations have found that having a greater portion of family within one’s social network is associated with lower cognition (Li & Dong, 2018; Sharifian et al, 2019). Furthermore, having a higher number of close friends, but not children or neighbors, has been linked to better global cognition (Wang, He, & Dong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, nearly 75′ of cognitively normal individuals aged 70–79 years are free of significant amyloid on PET imaging [6]. Along with this biomarker research, numerous studies have reported that modifiable behaviors such as lifestyle factors, social contacts, and community activities are also related to an increased risk for cognitive impairment, although the results have shown varying degrees and strengths of these relationships [4, 7, 8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous qualitative investigations found that distinguished from the emphasis of friend-oriented social relationships in Western societies, intergenerational relationships are more important for the Chinese older people ( Dong, Chang, Wong, & Simon, 2012 ). Perceived inadequate intergenerational support and shrank social network are key indicators for depressive symptoms and cognitive impairment for the Chinese older adults ( Dong, Li, & Hua, 2017 ; Li & Dong, 2018 ). Moreover, the role of personality on loneliness might vary across populations.…”
Section: Introductionmentioning
confidence: 99%